2015
DOI: 10.1242/jeb.118729
|View full text |Cite
|
Sign up to set email alerts
|

Focal enhancement of the skeleton to exercise correlates to mesenchymal stem cell responsivity rather than peak external forces

Abstract: Force magnitudes have been suggested to drive the structural response of bone to exercise. As importantly, the degree to which any given bone can adapt to functional challenges may be enabled, or constrained, by regional variation in the capacity of marrow progenitors to differentiate into bone-forming cells. Here, we investigate the relationship between bone adaptation and mesenchymal stem cell (MSC) responsivity in growing mice subject to exercise. First, using a force plate, we show that peak external force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 42 publications
4
44
0
1
Order By: Relevance
“…Each stride generated peak vertical substrate reaction forces between approximately 150% and 250% of the animal’s body weight (Roberts and Scales, 2002). This exercise routine constitutes a substantial increase in high-magnitude limb loading events relative to the normally sedentary activity patterns of laboratory turkeys (Fritton et al, 2000), and it is consistent with prior exercise studies that have revealed statistically significant musculoskeletal tissue changes in galliform birds (Buchanan and Marsh, 2001, 2002), as well as in mammals (Wallace et al, 2015). All subjects were euthanized by 18–19 months of age and their femora were extracted.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Each stride generated peak vertical substrate reaction forces between approximately 150% and 250% of the animal’s body weight (Roberts and Scales, 2002). This exercise routine constitutes a substantial increase in high-magnitude limb loading events relative to the normally sedentary activity patterns of laboratory turkeys (Fritton et al, 2000), and it is consistent with prior exercise studies that have revealed statistically significant musculoskeletal tissue changes in galliform birds (Buchanan and Marsh, 2001, 2002), as well as in mammals (Wallace et al, 2015). All subjects were euthanized by 18–19 months of age and their femora were extracted.…”
Section: Methodssupporting
confidence: 85%
“…In a diversity of animals including rodents (e.g., Wallace et al, 2015), ruminants (e.g., Lieberman et al, 2003; Barak et al, 2011), swine (e.g., Lieberman, 1996), and now turkeys, loadbearing forms of exercise such as running, particularly if they occur during the growing years, have been shown to enhance bone formation and augment diaphyseal robusticity and trabecular architecture, providing empirical support for the model within which paleoanthropologists commonly infer ancient human activity levels from these structural features of limb bone remains. Diaphyseal and trabecular structure are strongly affected by intrinsic factors such as age, sex, and genetics, but in studies of human skeletal remains in which these non-mechanical factors can be carefully evaluated and convincingly argued to not underlie observed morphological patterns, ample evidence from animal experiments suggests that such patterns may be due to variation in physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…These regional differences in the effects of LMS on BMD may relate to the proximity of the device to body region, with potential loss of vibratory energy as the signal travels from the distal lower extremity to the trunk, 47 or to differences in capacity to respond to mechanical signals, with some regions more attuned to functional adaptation than others. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Given that the marrow volume of the femur is approximately twice that of the tibia, this suggests that an early stage in the pathogenesis of the disease may be to crowd out the healthy marrow, and once that occurs, marrow necrosis begins as aggravated by the absence of a viable marrow to support it. Alternatively, it is entirely possible that spatially distinct marrow populations may account for the differential progression of the tumor in the tibia vs. the femur, as well as the distinct responses of these bones to the mechanical intervention (60). Extrapolating to the clinic, it suggests that any intervention that slows the crowding of the marrow by the tumor would, naturally, slow the inevitable advance of necrosis that follows.…”
Section: Discussionmentioning
confidence: 99%